2017
DOI: 10.1177/1357633x17713140
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of prehospital telehealth utilization

Abstract: Objective There has been moderate evidence of telehealth utilization in the field of emergency medicine, but less is known about telehealth in prehospital emergency medical services (EMS). The objective of this study is to explore the extent, focus, and utilization of telehealth for prehospital emergency care through the analysis of published research. Methods The authors conducted a systematic literature review by extracting data from multiple research databases (including MEDLINE/PubMed, CINAHL Complete, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 71 publications
1
37
0
3
Order By: Relevance
“…79,80 Previous reviews in acute trauma care identified telemedical assistance by remote medical expertise as prominent telemedical modality and included mostly cases studies. These findings match those observed by Winburn et al, 81 that the most used telemedical application in prehospital care was real-time video-conferencing. Rogers et al included also four of the studies that were analysed in this review, 64,65,68,71 but categorized them into general care.…”
Section: Principal Findingssupporting
confidence: 91%
“…79,80 Previous reviews in acute trauma care identified telemedical assistance by remote medical expertise as prominent telemedical modality and included mostly cases studies. These findings match those observed by Winburn et al, 81 that the most used telemedical application in prehospital care was real-time video-conferencing. Rogers et al included also four of the studies that were analysed in this review, 64,65,68,71 but categorized them into general care.…”
Section: Principal Findingssupporting
confidence: 91%
“…The results suggest there are significant opportunities for wider diffusion of telehealth in pre-hospital care. The authors concluded that despite positive trends, telehealth utilisation in pre-hospital emergency care is fairly limited given the sheer number of EMS agencies worldwide [71]. In the study of Langabeer et al, patient care enabled by telehealth in a pre-hospital environment was more cost-effective alternative compared to the traditional EMS 'treat and transport to ED' model.…”
Section: Proposals For Systemic Solutionsmentioning
confidence: 99%
“…There exists evidence to suggest that teleconsultation assessment bene ts virtually all medical scenarios, including ambulance transportation [8]. In a prehospital setting, the support TM lends to the ambulance team is associated with a reduction in ED referral [9]. Video communication between the ambulance and the ED may boost the local staff's perception of clinical status and jump-start triage [10].…”
Section: Introductionmentioning
confidence: 99%